On quantitative spatial economic models - Kristian Behrens; Yasusada Murata (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
Quantitative spatial economics (QSE) specifies various components such as preferences, production technology, and frictions for the movement of goods, people, and ideas. Despite the long literature on endogenous location decisions, the question of how these specifications affect resulting spatial equilibria has not been systematically explored. In this paper we start with workhorse models of QSE based on different specifications of preferences and show that spatial equilibria in those models can be generated using the conditional logit model by McFadden (1974). Our result suggests that existing models of QSE have a common origin in one of the oldest location choice models.
Keywords: 330